A corrosion-resistant aluminum alloy composite material

By pretreating silicon nitride and using multi-stage adjustable microarc oxidation voltage, the problem of uneven distribution of inorganic micro-nanoparticles in the microarc oxidation film layer is solved, and the corrosion resistance and wear resistance of aluminum alloy oxide film are significantly improved. performance.

CN113652724BActive Publication Date: 2025-02-18SICHUAN JIXIN CENTURY METAL SURFACE TREATMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110964183.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-08-21
Publication Date
2025-02-18
Estimated Expiration
2041-08-21

AI Technical Summary

Technical Problem

In the prior art, the inorganic micro-nanoparticles of the micro-arc oxidized ceramic film layer are unevenly distributed, resulting in insufficient corrosion resistance and wear resistance of the film layer and a high friction coefficient.

Method used

By pretreating silicon nitride and using a multi-stage adjustable microarc oxidation voltage, the distribution of inorganic micro-nanoparticles in the microarc oxidation film is improved, so that they are evenly dispersed in the film layer.

Benefits of technology

The corrosion resistance and wear resistance of the aluminum alloy oxide film are significantly improved, the stability and density of the film layer are improved, and the friction coefficient is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113652724B_ABST
    Figure CN113652724B_ABST
Patent Text Reader

Abstract

The present invention provides a corrosion-resistant aluminum alloy composite material, which effectively improves the distribution of inorganic micro-nano particles in a micro-arc oxidation film by pre-treating silicon nitride and adjusting the micro-arc oxidation voltage in multiple stages, so that the inorganic micro-nano particles are effectively and evenly dispersed in the micro-arc oxidation film layer, significantly improving the corrosion resistance and wear resistance of the aluminum alloy oxide film, especially improving the stability of the micro-arc oxidation film and reducing its volatility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a corrosion-resistant aluminum alloy composite material, and in particular to a method for treating an aluminum alloy by micro-arc oxidation. Background Art

[0002] Microarc oxidation (MAO), also known as plasma electrolytic oxidation (PEO), is a new technology for preparing ceramic coatings in an aqueous electrolyte environment by applying high voltage on the surface of metals (Ti, Al, Mg, Zr, Nb and Ta, etc.). The method is simple, the coating growth efficiency is high, and the prepared ceramic coating has excellent thermal and mechanical properties. Studies have shown that the ceramic film layer is metallurgically bonded to the substrate and has good bonding strength. Its typical structure consists of an internal dense layer and an external loose porous layer, and generally has a high hardness. The aluminum alloy micro-arc oxidation ceramic film layer is mainly Al2O3, and the hardness can reach 800~2000HV; the magnesium alloy micro-arc oxidation ceramic film layer is mainly MgO, and the hardness can reach 300~600HV; the titanium alloy micro-arc oxidation ceramic film layer is mainly TiO2, and the hardness can reach 600~800HV. The ceramic film layer significantly improves the wear resistance of the surface due to the increase in hardness. However, the existence of inherent micro-arc discharge channels and cracks in the ceramic film layer makes the surface present a loose and porous structure, and exhibits a higher friction coefficient under dry friction conditions. In the process of tribological application, the higher friction coefficient will not only accelerate its own wear failure, but also aggravate the wear of the dual material. In the prior art, in order to improve the wear resistance of the micro-arc oxidation ceramic film layer, stable phase micro-nanoparticles (SiO2, Cr203, ZrO2, SiC, Si3N4, TiC, etc.) with high hardness are usually added directly to the electrolyte for micro-arc oxidation. The addition of particles increases the hardness of the composite coating, and the density is also improved to a certain extent, thereby making the composite coating exhibit better wear resistance.

[0003] For example, CN109868386 A discloses a wear-resistant material, in which aluminum nitride, aluminum oxide, molybdenum disilicide, and graphite powder particles are evenly distributed in an aluminum alloy matrix, and a composite micro-arc oxidation layer is distributed on the surface of the aluminum alloy matrix. Aluminum nitride, aluminum oxide, and molybdenum disilicide have high hardness, which significantly improves the hardness and wear resistance of the material, and graphite powder can improve the friction reduction. The composite micro-arc oxidation layer on the surface can effectively improve the wear resistance and corrosion resistance of the alloy surface.

[0004] For example, CN106995931 A discloses a method for preparing a composite ceramic layer of aluminum alloy micro-arc oxidation, wherein the aluminum alloy substrate is pretreated: the aluminum alloy substrate is polished, the surface oxide layer is removed and polished, the grease on the surface of the aluminum alloy substrate is removed, ultrasonic cleaning is performed, and then drying is performed; SiC nanoparticles and polyethylene glycol are added to distilled water, ultrasonic vibration is performed, SiC nanoparticles are dispersed, and SiC dispersion is prepared; SiC dispersion is added during the preparation of the electrolyte, so that the concentration of SiC in the electrolyte reaches 2g / L, and the solvent of the electrolyte is distilled water; the electrolyte obtained in step c is used to micro-arc oxidize the aluminum alloy substrate, and the aluminum alloy substrate is used as the anode. By adding SiC nanoparticles to the electrolyte, the functional particles are attempted to be sintered in the ceramic layer, so that the various performances of the ceramic layer are significantly improved, making it denser and having a smaller friction coefficient during friction and wear.

[0005] CN112195491 A A method for preparing a SiC-Al2O3 coating based on micro-arc oxidation, the method comprising substrate pretreatment, solution preparation, composite ceramic coating preparation and ceramic layer post-treatment, the method ultimately obtaining a SiC-Al2O3 composite layer with an inner layer of an Al2O3 ceramic layer and an outer layer of a SiC ceramic layer, and the thickness of the composite layer is 30 to 400 μm; wherein, in the solution preparation, a deionized water solution with KOH-Na2SiO3-(NaPO3)6-Na2WO4 as the main component and a mixed solution of an alkaline silica sol solution, a water-soluble phenolic resin and nano-SiC particles are used. The method of the present invention prepares two composite ceramic layers on the surface of an aluminum alloy workpiece through a single micro-arc oxidation process. The method has high preparation efficiency, low production energy consumption, low preparation cost, and saves preparation time. At the same time, the method does not require sealing treatment, the bonding strength between the ceramic layers and the ceramic layers, and between the ceramic layers and the substrate is high, the density of the composite ceramic coating is good, and the overall wear resistance, corrosion resistance, heat insulation and ablation resistance of the aluminum alloy workpiece are excellent.

[0006] The following problems can be clearly drawn from the above-mentioned prior art patents: (1) People in the art should know that when inorganic micro-nano particles are added to the micro-arc oxidation electrolyte, the dispersion stability of the micro-nano particles in the electrolyte directly affects the film quality of the composite film layer. If the water solubility and dispersion of the inorganic micro-nano particles are low, it is easy to cause uneven composition and thickness of the composite film layer. The above-mentioned patents usually use organic nanoparticles to disperse the inorganic nanoparticles in the electrolyte, which can directly affect the film quality of the composite film layer.

[0007] Mechanical, ultrasonic and surface modification are used to improve the dispersion stability of particles and the dispersibility of inorganic nanoparticles, which is beneficial for the particles to enter the ceramic film layer. However, there is little research on how to obtain highly dispersed inorganic micro-nanoparticles in detail; (2) The size and concentration of micro-nanoparticles directly affect the distribution of inorganic micro-nanoparticles in the micro-arc oxidation film. For example, particles with smaller particle sizes are more likely to appear in discharge channels, cracks and other locations, while particles with larger particle sizes often only have a higher content on the surface of the composite film layer. The distribution of inorganic particles will directly affect the anisotropic stability and volatility of the composite micro-arc oxidation film. Summary of the invention

[0008] In view of the problems existing in the above prior art, the purpose of the present invention is to provide a corrosion-resistant aluminum alloy composite material, which effectively improves the distribution of inorganic micro-nano particles in the micro-arc oxidation film through pretreatment of silicon nitride and multi-stage adjustable micro-arc oxidation voltage, so that the inorganic micro-nano particles are effectively and evenly dispersed in the micro-arc oxidation film layer, significantly improving the corrosion resistance and wear resistance of the aluminum alloy oxide film, especially improving the stability of the micro-arc oxidation film and reducing its volatility.

[0009] A corrosion-resistant aluminum alloy composite material, wherein a silicon nitride composite oxide film is provided on the surface of the aluminum alloy by a micro-arc oxidation method, and the silicon nitride in the composite oxide film is highly uniformly dispersed, and the micro-arc oxidation method is a segmented micro-arc oxidation treatment:

[0010] Phase I: bidirectional voltage is used, with a forward voltage of 400V, a reverse voltage of 200V, a positive and negative duty cycle of 20%, a pulse number ratio of 1:1, and a time of 90s;

[0011] Phase II: bidirectional voltage is used, with a forward voltage of 500V, a reverse voltage of 150V, a positive and negative duty cycle of 10%, a pulse number ratio of 1:1, and a time of 60s;

[0012] Phase III: bidirectional voltage is used, with a forward voltage of 600V, a reverse voltage of 100V, a positive and negative duty cycle of 5%, a pulse number ratio of 1:1, and the time required for the current density to reach the peak value. The current density range is 110-130mA / cm 2 ;

[0013] Stage IV: a unidirectional voltage of 400 V is used. The duration of this stage is 3-5 minutes after the formation of a stable current. The density of the stable current is 15-18 mA / cm 2 .

[0014] Furthermore, the aluminum alloy is pretreated, and the pretreatment includes mechanical grinding, degreasing and acid treatment, wherein the degreasing is performed using 12wt.% NaOH, 75 oC for 7 min, the acid wash was done using 25 wt.% HNO3 for 1 min, and then washed with deionized water.

[0015] Furthermore, the nanometer size of the silicon nitride is 20-60 nm, and the silicon nitride is surface treated to obtain a 2-4 wt.% silicon nitride suspension aqueous solution.

[0016] Furthermore, the surface treatment is

[0017] (1) Take 2-4 g of Si3N4 nanoparticles and place them in a three-necked flask. Add 40 mL of 98% H2SO4 and 20 mL of 65% HNO3. o C reflux for 6 h.

[0018] (2) Wash by ultracentrifugation at 8000-10000 rpm multiple times until neutral, and freeze-dry in vacuum;

[0019] (3) The dried Si3N4 is placed in deionized water, and then an AES surfactant is added at room temperature and stirred to obtain a 2-4 wt.% silicon nitride suspension aqueous solution.

[0020] Further, the AES surfactant

[0021] The dosage is 1wt.%.

[0022] Further, the micro-arc oxidation solution is composed of 9-10 g / L sodium silicate, 3-4 g / L sodium tungstate, 1-1.5 g / L potassium hydroxide, and 2-3 g / L LEDTA-2Na, and the balance is 2-4 wt.% Si3N4 suspension aqueous solution, and HNO3 is used to adjust the pH to 11±1. The temperature of the micro-arc oxidation is 20-25 o C, stirring speed is 120-150rpm.

[0023] Furthermore, the corrosion-resistant aluminum alloy composite material is polished after the micro-arc oxidation treatment, and the polishing is performed by using 400#, 800#, 1200# and 2000# sandpaper in sequence.

[0024] Furthermore, the surface roughness obtained by polishing is Ra=0.3±0.1 μm.

[0025] Regarding the dispersibility of the inorganic nanoparticles of the present invention, the inorganic nanoparticles selected in the present invention are 20-60 nm silicon nitride, and the hydrophilic groups on the surface of silicon nitride are relatively few, so it is necessary to perform hydrophilic modification on the surface. 2-4 g of Si3N4 nanoparticles are placed in a three-necked flask, 40 mL of 98% H2SO4 and 20 mL of 65% HNO3 are added, and the mixture is stirred at 100 °C. o C reflux treatment for 6 h, after the silicon nitride is treated with mixed acid, acidic functional groups such as carboxyl, hydroxyl, aldehyde, etc. are formed on the surface of the inorganic particles. Since the inorganic particles are nanometer-sized, it is not suitable to use filtering and washing, so centrifugal treatment is adopted, and ultracentrifugal washing is performed at 8000-10000rpm for many times until neutral. Since the specific surface area of ​​the nanoparticles is relatively high, in order to prevent agglomeration, it is not suitable to use ordinary drying, but vacuum freeze drying is used, and then the dried Si3N4 is placed in deionized water, and AES surfactant is added at room temperature, and stirred to obtain a 2-4wt.% Si3N4 suspension aqueous solution, wherein the amount of AES surfactant is 1wt.%. When the Si3N4 is in the electrolyte pH of the present invention = 10-12, its particles The Zetapotential is -46.4~-48.2mV, that is, the Si3N4 can be highly dispersed in the electrolyte, that is, the present invention introduces hydrophilic groups on the surface of silicon nitride through acidic modification, and then adds the non-ionic surfactant AES to the solution. Although theoretically adding anionic surfactants can more significantly increase the electronegativity of inorganic particles, AES has both ethoxy and sulfonic acid groups, that is, it has both anionic and non-ionic surfactant properties, and has stronger alkali resistance, and is more suitable as the surfactant additive of the present invention.

[0026] The micro-arc oxidation process generally includes the following processes: the first stage: a large number of bubbles are generated, and small points of micro-arcs are generated. In this process, an oxide film is mainly generated, and the thickness of the oxide film has obvious unevenness. The second stage: due to the obvious unevenness of the thickness of the oxide film, the oxide film will simultaneously break down the relatively thin and weaker tiny areas in the oxide film under a strong voltage. Due to the instantaneous high temperature of the breakdown site, there are molten or even gasified aluminum oxide and aluminum in the high area, which then react with the electrolyte to form aluminum oxide, causing these relatively thin and weaker tiny areas to become thicker. In this stage, the current continues to increase, and the third stage is passed when the current increases to the peak; the third stage: due to the relatively thin and weaker tiny areas in the early stage becoming thicker, under a strong voltage, the discharge will be transferred to other relatively thin areas. After multiple discharges, the original smaller pores are connected to each other to form larger discharge pores. The number of pores increases significantly, and the thickness also increases significantly, resulting in a significant increase in resistance, that is, a significant decrease in current. The fourth stage: in this stage, only sporadic tiny sparks can be seen. If the power is turned on for a long time, the current will not change significantly, that is, the current is stable.

[0027] The composite micro-arc oxidation process is basically similar to the ordinary micro-arc oxidation process. The only difference lies in the participation of nanoparticles. First, the inorganic nanoparticles are surface modified and surface active, and are negatively charged in the micro-arc oxidation alkaline electrolyte. Secondly, the negatively charged nanoparticles are adsorbed onto the surface of the anode aluminum under the action of the electric field. Then, an anodic oxide film is formed and the nanoparticles are captured during the first stage. Then, local melting begins in the second stage. During this process, the nanoparticles are randomly coated in the oxide film, and then the third and fourth stages are carried out. In short, the whole process is that inorganic particles are deposited on the anode surface due to electronegativity, and the anode surface repels inorganic particles due to spark discharge, and then forms a random balance. This causes inorganic particles, especially extremely small nano-sized inorganic particles, to be preferentially distributed in anti-electric pores and cracks, resulting in uneven distribution of inorganic particles in the entire micro-arc oxidation film. This is also the technical problem to be solved by the present invention. From the above process, it can be seen that the first and second stages of micro-arc oxidation are the key periods for the participation of inorganic particles. Therefore, the relative position of the discharge pores is improved by segmented voltage, thereby achieving uniform distribution of inorganic particles in the micro-arc oxidation layer.

[0028] The process of segmented micro-arc oxidation treatment is as follows:

[0029] Phase I: bidirectional voltage is used, with a forward voltage of 400V, a reverse voltage of 200V, a positive and negative duty cycle of 20%, a pulse number ratio of 1:1, and a time of 90s;

[0030] Phase II: bidirectional voltage is used, with a forward voltage of 500V, a reverse voltage of 150V, a positive and negative duty cycle of 10%, a pulse number ratio of 1:1, and a time of 60s;

[0031] Phase III: bidirectional voltage is used, with a forward voltage of 600V, a reverse voltage of 100V, a positive and negative duty cycle of 5%, a pulse number ratio of 1:1, and the time required for the current density to reach the peak value. The current density range is 110-130mA / cm 2 ;

[0032] Stage IV: a unidirectional voltage of 400 V is used. The duration of this stage is 3-5 minutes after the formation of a stable current. The density of the stable current is 15-18 mA / cm 2 .

[0033] By increasing the forward voltage and reducing the reverse voltage in stages, the uniformity of adsorption of negatively charged inorganic particles on the anode surface can be effectively dispersed, and the first and second stages of micro-arc oxidation are mainly adjusted. Since the third and fourth stages are mainly to increase the thickness of micro-arc oxidation, they are ordinary micro-arc oxidation processes and no adjustment is made. In addition, an obvious loose porous layer will be formed in the third and fourth stages. The porous layer is not conducive to improving the corrosion resistance and wear resistance of the aluminum alloy. Since the porous layer is completely disordered, it is even more unfavorable to improve the isotropic stability of the aluminum alloy and reduce its physical and chemical stability. It is removed by polishing. The polishing is to use 400#, 800#, 1200# and 2000# sandpaper for grinding and polishing in sequence. The loose layer of the ceramic film layer is removed by grinding and polishing technology, and the exposed dense layer exhibits higher corrosion resistance, hardness and lower roughness.

[0034] Beneficial technical effects: (1) By acid reflux and surfactant treatment, the dispersibility of silicon nitride in aqueous solution is effectively improved while removing oxides or impurities on the surface of silicon nitride. When dispersed in an alkaline electrolyte, its Zeta negative potential is effectively reduced, thereby obtaining a highly dispersed silicon nitride suspension. The highly dispersed state is beneficial to the distribution of silicon nitride in composite micro-arc oxidation.

[0035] (2) Through the multi-stage adjustable micro-arc oxidation voltage, the distribution of inorganic micro-nano particles in the micro-arc oxidation film is effectively improved, so that the inorganic micro-nano particles are effectively and evenly dispersed in the micro-arc oxidation film layer, which significantly improves the corrosion resistance and wear resistance of the aluminum alloy oxide film, especially improves the stability of the micro-arc oxidation film and reduces its volatility. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Attached Figure 1 This is a scanning transmission image of the micro-arc oxidation film obtained in Comparative Example 1.

[0037] Attached Figure 2 This is a scanning transmission image of the micro-arc oxidation film obtained in Example 2 of the present invention.

[0038] Attached Figure 3 This is a scanning transmission nitrogen element analysis diagram of the micro-arc oxidation film obtained in Example 2 of the present invention and Comparative Example 1.

[0039] Attached Figure 4 This is a graph showing the change in roughness Ra during the segmented voltage micro-arc oxidation process of the present invention. DETAILED DESCRIPTION Example 1

[0040] An aluminum alloy composite oxide film is prepared by the following method

[0041] (1) Surface pretreatment of the aluminum alloy; the surface treatment includes mechanical grinding, degreasing and acid treatment, wherein the degreasing is performed using 12wt.% NaOH, 75 o C for 7 min, the acid wash was done using 25 wt.% HNO3 for 1 min, and then washed with deionized water.

[0042] (2) Preparation of Si3N4 suspension and micro-arc oxidation electrolyte:

[0043] Preparation method of the Si3N4 suspension:

[0044] (a) Take 2 g of Si3N4 nanoparticles with a nanometer size of 20-60 nm, place them in a three-necked flask, add 40 mL of 98% H2SO4 and 20 mL of 65% HNO3, and stir at 100 °C. o C reflux for 6 h.

[0045] (b) Wash by ultracentrifugation at 8000 rpm multiple times until neutral, and freeze-dry in vacuum.

[0046] (c) The dried Si3N4 was placed in deionized water, and then an AES surfactant was added at room temperature and stirred to obtain a 2 wt.% Si3N4 suspension aqueous solution, wherein the amount of the AES surfactant was 1 wt.%.

[0047] The micro-arc oxidation electrolyte consists of 9g / L sodium silicate, 3g / L sodium tungstate, 1g / L potassium hydroxide, and 2g / LEDTA-2Na, with the remainder being a 2wt.% Si3N4 suspension aqueous solution, and HNO3 is used to adjust the pH to 11.

[0048] (3) Using aluminum alloy as anode, implement segmented micro-arc oxidation treatment:

[0049] The stepwise micro-arc oxidation process is as follows: the temperature during the micro-arc oxidation process is 20 o C, stirring speed is 120 rpm.

[0050] Phase I: bidirectional voltage is used, with a forward voltage of 400V, a reverse voltage of 200V, a positive and negative duty cycle of 20%, a pulse number ratio of 1:1, and a time of 90s.

[0051] Phase II: bidirectional voltage is used, with a forward voltage of 500V, a reverse voltage of 150V, a positive and negative duty cycle of 10%, a pulse number ratio of 1:1, and a time of 60s.

[0052] Phase III: bidirectional voltage is used, with a forward voltage of 600V, a reverse voltage of 100V, a positive and negative duty cycle of 5%, a pulse number ratio of 1:1, and the time required for the current density to reach its peak value.

[0053] Stage IV: Use unidirectional voltage with a voltage of 400V. This stage lasts for 3-5 minutes after a stable current is formed.

[0054] (4) Polishing treatment,

[0055] The polishing is performed by sequentially using 400#, 800#, 1200# and 2000# sandpapers. Example 2

[0056] An aluminum alloy composite oxide film is prepared by the following method

[0057] (1) Surface pretreatment of the aluminum alloy; the surface treatment includes mechanical grinding, degreasing and acid treatment, wherein the degreasing is performed using 12wt.% NaOH, 75 o C for 7 min, the acid wash was done using 25 wt.% HNO3 for 1 min, and then washed with deionized water.

[0058] (2) Preparation of Si3N4 suspension and micro-arc oxidation electrolyte:

[0059] Preparation method of the Si3N4 suspension:

[0060] (a) Take 3 g of Si3N4 nanoparticles with a nanometer size of 20-60 nm, place them in a three-necked flask, add 40 mL of 98% H2SO4 and 20 mL of 65% HNO3, and stir at 100 °C. o C reflux for 6 h.

[0061] (b) Wash by ultracentrifugation at 9000 rpm multiple times until neutral, and freeze-dry in vacuum.

[0062] (c) The dried Si3N4 was placed in deionized water, and then an AES surfactant was added at room temperature and stirred to obtain a 3 wt.% Si3N4 suspension aqueous solution, wherein the amount of the AES surfactant was 1 wt.%.

[0063] The micro-arc oxidation electrolyte consists of 9.5 g / L sodium silicate, 3.5 g / L sodium tungstate, 1.25 g / L potassium hydroxide, and 2.5 g / L LEDTA-2Na, with the remainder being a 3 wt.% Si3N4 suspension aqueous solution, and HNO3 is used to adjust the pH to 11.

[0064] (3) Using aluminum alloy as anode, implement segmented micro-arc oxidation treatment:

[0065] The stepwise micro-arc oxidation process is as follows: the temperature during the micro-arc oxidation process is 23 o C, stirring speed is 135 rpm.

[0066] Phase I: bidirectional voltage is used, with a forward voltage of 400V, a reverse voltage of 200V, a positive and negative duty cycle of 20%, a pulse number ratio of 1:1, and a time of 90s.

[0067] Phase II: bidirectional voltage is used, with a forward voltage of 500V, a reverse voltage of 150V, a positive and negative duty cycle of 10%, a pulse number ratio of 1:1, and a time of 60s.

[0068] Phase III: Bidirectional voltage is used, with a forward voltage of 600V, a reverse voltage of 100V, a positive and negative duty cycle of 5%, a pulse ratio of 1:1, and the time required for the current density to reach the peak value. After multiple tests, the time for the peak current density to appear is 52s, and the peak current value reached is 123mA / cm 2 .

[0069] Stage IV: unidirectional voltage is used, the voltage is 400V, the time of this stage is 3-5min after the formation of stable current, the time of forming stable current is 13.5min, and the density of the stable current is 16.4 mA / cm 2 .

[0070] (4) Polishing treatment,

[0071] The polishing is performed by sequentially using 400#, 800#, 1200# and 2000# sandpapers. Example 3

[0072] An aluminum alloy composite oxide film is prepared by the following method

[0073] (1) Surface pretreatment of the aluminum alloy; the surface treatment includes mechanical grinding, degreasing and acid treatment, wherein the degreasing is performed using 12wt.% NaOH, 75 o C for 7 min, the acid wash was done using 25 wt.% HNO3 for 1 min, and then washed with deionized water.

[0074] (2) Preparation of Si3N4 suspension and micro-arc oxidation electrolyte:

[0075] Preparation method of the Si3N4 suspension:

[0076] (a) Take 4 g of Si3N4 nanoparticles with a nanometer size of 20-60 nm, place them in a three-necked flask, add 40 mL of 98% H2SO4 and 20 mL of 65% HNO3, and stir at 100 °C. o C reflux for 6 h.

[0077] (b) Wash by ultracentrifugation at 10,000 rpm multiple times until neutral, and freeze-dry in vacuum.

[0078] (c) The dried Si3N4 was placed in deionized water, and then an AES surfactant was added at room temperature and stirred to obtain a 4 wt.% Si3N4 suspension aqueous solution, wherein the amount of the AES surfactant was 1 wt.%.

[0079] The micro-arc oxidation electrolyte is composed of 10g / L sodium silicate, 4g / L sodium tungstate, 1.5g / L potassium hydroxide, and 3g / LEDTA-2Na, and the balance is 4wt.% Si3N4 suspension aqueous solution, and HNO3 is used to adjust the pH to 11±1. (3) Using aluminum alloy as the anode, perform segmented micro-arc oxidation treatment:

[0080] The stepwise micro-arc oxidation process is as follows: the temperature during the micro-arc oxidation process is 25 o C, stirring speed is 150 rpm.

[0081] Phase I: bidirectional voltage is used, with a forward voltage of 400V, a reverse voltage of 200V, a positive and negative duty cycle of 20%, a pulse number ratio of 1:1, and a time of 90s.

[0082] Phase II: bidirectional voltage is used, with a forward voltage of 500V, a reverse voltage of 150V, a positive and negative duty cycle of 10%, a pulse number ratio of 1:1, and a time of 60s.

[0083] Phase III: bidirectional voltage is used, with a forward voltage of 600V, a reverse voltage of 100V, a positive and negative duty cycle of 5%, a pulse number ratio of 1:1, and the time required for the current density to reach the peak value. The current density range is 110-130mA / cm 2 .

[0084] Stage IV: a unidirectional voltage of 400 V is used. The duration of this stage is 3-5 minutes after the formation of a stable current. The density of the stable current is 15-18 mA / cm 2 .

[0085] (4) Polishing treatment,

[0086] The polishing is performed by sequentially using 400#, 800#, 1200# and 2000# sandpapers.

[0087] Comparative Example 1: An aluminum alloy composite oxide film is prepared by the following method:

[0088] (1) Surface pretreatment of the aluminum alloy; the surface treatment includes mechanical grinding, degreasing and acid treatment, wherein the degreasing is performed using 12wt.% NaOH, 75 o C for 7 min, the acid wash was done using 25 wt.% HNO3 for 1 min, and then washed with deionized water.

[0089] (2) Preparation of micro-arc oxidation electrolyte:

[0090] (3) Micro-arc oxidation treatment was carried out with aluminum alloy as the anode: the micro-arc oxidation electrolyte consisted of 9.5 g / L sodium silicate, 3.5 g / L sodium tungstate, 1.25 g / L potassium hydroxide, and 2.5 g / L LEDTA-2Na, and the remainder was a 3 wt.% Si3N4 suspension aqueous solution. The preparation method of the 3 wt.% Si3N4 suspension aqueous solution was exactly the same as that in Example 2. HNO3 was used to adjust the pH to 11. The voltage was a bidirectional voltage of 600 V, the positive and negative duty cycle was 10%, the pulse number ratio was 1:1, and the time was consistent with the total micro-arc oxidation time in Example 2.

[0091] (4) Polishing treatment,

[0092] The polishing is performed by sequentially using 400#, 800#, 1200# and 2000# sandpapers.

[0093] Comparative Example 2: An aluminum alloy composite oxide film is prepared by the following method:

[0094] (1) Surface pretreatment of the aluminum alloy; the surface treatment includes mechanical grinding, degreasing and acid treatment, wherein the degreasing is performed using 12wt.% NaOH, 75 o C for 7 min, the acid wash was done using 25 wt.% HNO3 for 1 min, and then washed with deionized water.

[0095] (2) Preparation of Si3N44 suspension and micro-arc oxidation electrolyte:

[0096] The preparation method of the Si3N4 suspension is as follows: 3 g of Si3N4 nanoparticles with a nanometer size of 20-60 nm are taken and directly placed in an aqueous solution.

[0097] The micro-arc oxidation electrolyte consists of 9.5 g / L sodium silicate, 3.5 g / L sodium tungstate, 1.25 g / L potassium hydroxide, and 2.5 g / L LEDTA-2Na, with the remainder being a 3 wt.% Si3N4 suspension aqueous solution, and HNO3 is used to adjust the pH to 11.

[0098] (3) Using aluminum alloy as the anode, micro-arc oxidation treatment was carried out: the micro-arc oxidation electrolyte consisted of 9.5 g / L sodium silicate, 3.5 g / L sodium tungstate, 1.25 g / L potassium hydroxide, and 2.5 g / L LEDTA-2Na, the remainder being a 3 wt.% Si3N4 suspension aqueous solution, and the pH was adjusted to 11 with HNO3. The voltage was 600 V bidirectional voltage, the positive and negative duty cycle was 10%, the pulse number ratio was 1:1, and the time was consistent with the total micro-arc oxidation time of Example 2.

[0099] (4) Polishing treatment,

[0100] The polishing is performed by sequentially using 400#, 800#, 1200# and 2000# sandpapers.

[0101] Comparative Example 2 uses commercial silicon nitride to prepare an aqueous solution, and the rest is similar to Comparative Example 1.

[0102] After surface treatment, the aluminum material used in the present invention has a surface roughness of about Ra = 0.1, after micro-arc oxidation, the roughness is about 1.7-1.8, and after polishing, the roughness is reduced to about 0.3. Figure 4 In addition, there is Figure 1 and attached Figure 2 It can be seen that, in comparison, the micro-arc oxidation film treated by segmented micro-arc oxidation is denser, and the corresponding corrosion resistance is better.

[0103] The samples prepared in Example 2 and Comparative Examples 1-2 were tested.

[0104] The aluminum alloy substrate is stripped by an electrochemical method. The main reason is that the micro-arc oxidation film has strong corrosion resistance and the aluminum material has weak corrosion resistance. The aluminum material is slowly corroded by electrochemical means, and the pH value of the electrolyte is controlled at any time to be 6-6.5. The aluminum material can be effectively stripped, leaving only the micro-arc oxidation film. The micro-arc oxidation film is cut into 1cm*1cm sheets, and the corrosion current density thereof is tested respectively. The number of tests is 15, and the corrosion voltages of the substrate, comparative example 1, comparative example 2, and embodiment 2 are -1.36V, -0.78V, -0.97V, and -0.72V, respectively, and the corrosion currents are 10.51μAcm -2 、0.48μAcm -2 、5.35μAcm -2 、0.38μAcm -2It can be clearly seen that the corrosion currents of Comparative Example 1 and Example 2 are significantly higher than those of Comparative Example 2. The main reason is that the silicon nitride described in Comparative Example 2 obviously floats on the surface of the aqueous solution and therefore cannot participate in the micro-arc oxidation, that is, it is impossible to achieve effective composite micro-arc oxidation deposition, which is similar to the simple micro-arc oxidation treatment of aluminum alloy. The difference in corrosion current between Comparative Example 1 and Example 2 is less than 1%, and as shown in the following table, some current densities are almost the same, that is, micro-arc oxidation by segmented voltage has a positive effect on corrosiveness, but it is not obvious. However, it can be seen from the average deviation that the segmented voltage treatment can effectively improve the dispersion of silicon nitride in the micro-arc oxidation film, that is, the average deviation is very low, that is, the isotropic uniformity is good. In addition, the average deviation of Comparative Example 2 is also higher than that of Comparative Example 1. The main reason is that the silicon nitride in Comparative Example 2 hardly participates in the micro-arc oxidation reaction, that is, the isotropic uniformity is relatively high, while in Comparative Example 1, due to the participation of silicon nitride, the distribution degree of the silicon nitride will significantly affect the isotropic uniformity of the micro-arc oxidation film, that is, the pretreatment of silicon nitride and the segmented micro-arc oxidation treatment of the present invention can improve the corrosion resistance of the aluminum alloy while further improving the uniformity and stability of the corrosion resistance of the micro-arc oxidation film of the aluminum alloy.

[0105]

[0106] In order to further verify the effect of segmented voltage on the distribution of silicon nitride in micro-arc oxidation film, the N element is analyzed. Since the micro-arc oxidation solution contains silicon, it is not appropriate to use silicon to evaluate the distribution of silicon nitride. Nitrogen mainly comes from silicon nitride and EDTA-2Na. There is very little EDTA-2Na in the micro-arc oxidation film. Therefore, the energy spectrum of nitrogen can effectively characterize the distribution state of silicon nitride in the micro-arc oxidation film, as shown in the attached figure. Figure 3 As shown, attached Figure 3 The above figure is a spectrum of Example 2 of the present invention. It can be clearly seen that in the micro-arc oxidation film, the distribution of the entire N element is very uniform. Figure 3 The figure below (Comparative Example 1) does not undergo segmented voltage micro-arc oxidation, and the distribution of nitrogen elements is obviously uneven. The closer to the aluminum material, the less nitrogen elements there are, and the farther away from the aluminum material, the more nitrogen elements there are, and the distribution on the left and right is also uneven.

[0107] Although the present invention has been described above by way of example with reference to the preferred embodiments, the present invention is not limited to such specific embodiments and can be appropriately modified within the scope of the protection scope of the present invention.

Claims

1. A corrosion-resistant aluminum alloy composite material, characterized in that The aluminum alloy surface is provided with a silicon nitride composite oxide film by a micro-arc oxidation method, and the silicon nitride in the composite oxide film is highly evenly dispersed. The micro-arc oxidation method is a segmented micro-arc oxidation treatment: Phase I: bidirectional voltage is used, with a forward voltage of 400V, a reverse voltage of 200V, a positive and negative duty cycle of 20%, a pulse ratio of 1:1, and a time of 90s; Phase II: bidirectional voltage is used, with a forward voltage of 500V, a reverse voltage of 150V, a positive and negative duty cycle of 10%, a pulse number ratio of 1:1, and a time of 60s; Phase III: bidirectional voltage is used, with a forward voltage of 600V, a reverse voltage of 100V, a positive and negative duty cycle of 5%, a pulse number ratio of 1:1, and the time required for the current density to reach the peak value. The current density range is 110-130mA / cm 2 ; Stage IV: a unidirectional voltage of 400 V is used. The duration of this stage is 3-5 minutes after the formation of a stable current. The density of the stable current is 15-18 mA / cm 2 ; The nanometer size of the silicon nitride is 20-60nm, and the silicon nitride is surface treated to obtain a 2-4wt.% silicon nitride suspension aqueous solution; The silicon nitride is surface treated as follows: (1) Take 2-4 g of Si3N4 nanoparticles, place them in a three-necked flask, add 40 mL of 98% H2SO4 and 20 mL of 65% HNO3, and reflux at 100 °C for 6 h under stirring. (2) Wash by ultracentrifugation at 8000-10000 rpm multiple times until neutral, and freeze-dry in vacuum; (3) placing the dried Si3N4 in deionized water, then adding AES surfactant at room temperature and stirring to obtain a 2-4wt.% silicon nitride suspension aqueous solution; The electrolyte used in the micro-arc oxidation method is composed of 9-10g / L sodium silicate, 3-4g / L sodium tungstate, 1-1.5g / L potassium hydroxide, and 2-3g / LEDTA-2Na, and the balance is 2-4wt.% Si3N4 suspension aqueous solution. HNO3 is used to adjust the pH to 11±1. The temperature of micro-arc oxidation is 20-25°C and the stirring speed is 120-150rpm. The aluminum alloy was pretreated as follows, including mechanical grinding, degreasing and pickling, wherein the degreasing was performed by using 12 wt.% NaOH and soaking at 75°C for 7 min, and the pickling was performed by soaking in 25 wt.% HNO3 for 1 min, followed by washing with deionized water.

2. The corrosion-resistant aluminum alloy composite material according to claim 1, characterized in that After the aluminum alloy is treated with micro-arc oxidation, it is polished using 400#, 800#, 1200# and 2000# sandpaper in sequence, and the surface roughness obtained by polishing is Ra=0.3±0.1μm.

3. The corrosion-resistant aluminum alloy composite material according to claim 1, characterized in that The amount of the AES surfactant used is 1 wt.%.

Citation Information

Patent Citations

  • Preparation method of aluminum alloy microarc oxidation composite ceramic layer

    CN106995931A

  • Wear resisting material and preparation method thereof

    CN109868386A

  • Preparation method of SiC-Al2O3 coating based on micro-arc oxidation

    CN112195491A

  • Electrolyte solution for preparing aluminum and aluminum alloy ceramic membrane through micro-arc oxidation technology

    CN104514027A

  • Aluminum alloy member for semiconductor liquid crystal manufacturing apparatus

    JP2010209411A